Determinants of Patients' Choice of Provider in Accessing Brucellosis Care among Pastoral Communities Adjacent to Lake Mburo National Park in Kiruhura District, Uganda - Kansiime, Catherine (Public Library of Science, 2014)
BACKGROUND: Brucellosis is the commonest zoonotic infection worldwide with symptoms similar to other febrile syndromes such as malaria and typhoid fever. It is often easily misdiagnosed, resulting in underreporting and misdirected treatments. Understanding of the factors that influence brucellosis care seeking is essential in enhancing its effective management. Our study sought to determine the factors associated with choice of provider in accessing care for brucellosis among pastoral communities in Uganda. METHODS: This was a cross-sectional survey involving 245 randomly selected respondents previously diagnosed and treated for brucellosis, two months before the study. They were enrolled from three sub-counties neighboring Lake Mburo National Park between December 2012 to April 2013. Data on socio-demographics, availability, accessibility, affordability and acceptability of health services were collected. A multivariable logistic regression model was fitted to determine association between independent and outcome variables using odds ratios and 95% confidence intervals with p-value≤0.05 considered statistically significant. RESULTS: Of the 245 respondents, 127(51.8%) sought health care at government facilities and the rest at private. Respondents who were less likely to choose a government facility were either single (OR: 0.50, CI: 0.26–0.97), had general weakness (OR: 0.09, CI: 0.01–0.72) or whom family took a decision (OR: 0.52, CI: 0.28–0.97). At multivariable analysis, choice of government facility was influenced by primary education (aOR: 0.46, CI: 0.22–0.97), having six to ten household members (aOR:3.71, CI:1.84–7.49), family advice (aOR:0.64, CI: 0.23–0.91), distance ≥10 kms (aOR:0.44, CI: 0.21–0.92), high costs at private clinics (aOR:0.01, CI:0.02–0.15) and no diagnosis at government facility (aOR:0.11, CI:0.01–0.97). Females were more likely to seek health care at government facilities, while those with tertiary education were less likely, after the first provider. CONCLUSIONS: Females and households with six to ten members were more likely to choose government facilities. Government facilities need to be equipped to attract more patients.